Model builder for diagnosis and simulation of hybrid dynamic systems: Application to railway rolling stock. (January 2021) - Six, B; Ould-Bouamama, B; Gehin, A L
This paper deals with a model builder for Hybrid Dynamic Systems (HDS), where technological components including sensors in an iconic format can be automatically dragged from a database and interconnected to produce the overall HDS, following industrial technological schemes. Once the model has been created, its consistency can be checked, and a block diagram simulation can be performed. The theory behind the software is based on Hybrid Bond Graphs (HBG), whose structural and causal properties will be exploited for the automatic generation of the diagnosis algorithms, which will be implemented online. Compared with developed programs for automated modeling of HDS, the presented methodology is valid for continuous and hybrid systems, and the HBG is used not only for block diagram simulation builders but also for the generation of Fault Detection and Isolation algorithms. The theory is illustrated by an industrial application that consists of the pneumo-electrical control of metro rolling stock.